Some observations on ticks (Acari : Ixodidae) infesting sheep in River Nile Province of Northern Sudan - B.M. Ahmed; A.M. El Hussein; A.O. El Khider (Onderstepoort Journal of Veterinary Research, 2005)
Five species of ixodid ticks were found in a cross-sectional survey in which 200 sheep were examined for ticks in River Nile Province, Sudan. Hyalomma anatolicum anatolicum was the predominant species (73.6 %), whereas ticks belonging to the Rhipicephalus sanguineus group (14.7 %), Rhipicephalus evertsi evertsi (9.1 %), Rhipicephalus simus (2 %) and Hyalomma dromedarii (0.5 %) were also found. The mean tick load was 11.2 per animal. In a subsequent longitudinal survey ticks were collected on a monthly basis from eight sentinel sheep that were introduced into the area. It was found that H. a. anatolicum almost disappeared during the hot period between April and August, whereas it's highest numbers were present in winter between November and February. It is concluded that there is only one generation of H. a. anatolicum per year, which may explain the yearround appearance of clinical cases of malignant ovine theileriosis indicating endemic instability of this disease in River Nile Province.